An Amino Acids Mixture Improves the Hepatotoxicity Induced by Acetaminophen in Mice. (26th June 2013) - Di Pierro, Francesco; Rossoni, Giuseppe
Abstract : Acetaminophen (APAP) is a widely used analgesic and antipyretic drug, but at high dose it leads to undesirable side effects, such as hepatotoxicity and nephrotoxicity. The aim of this study was to evaluate the protective role of DDM-GSH, a mixture of L-cysteine, L-methionine, and L-serine in a weight ratio of 2 : 1 : 1, in comparison to N-acetylcysteine (NAC), against acetaminophen- (APAP-) induced hepatotoxicity in mice. Toxicity was induced in mice by the intraperitoneal (ip) administration of low dose (2 mmol/kg) or high dose (8 mmol/kg) of APAP. DDM-GSH (0.4 to 1.6 mmol/kg) was given ip to mice 1 h before the APAP administration. The same was done with NAC (0.9 to 3.6 mmol/kg), the standard antidote of APAP toxicity. Mice were sacrificed 8 h after the APAP injection to determine liver weight, serum alanine aminotransferase (ALT), and total glutathione (GSH) depletion and malondialdehyde (MDA) accumulation in liver tissues. DDM-GSH improved mouse survival rates better than NAC against a high dose of APAP. Moreover, DDM-GSH significantly reduced in a dose-dependent manner not only APAP-induced increases of ALT but also APAP-induced hepatic GSH depletion and MDA accumulation. Our results suggest that DDM-GSH may be more potent than NAC in protecting the liver from APAP-induced liver injury.